Genotype–phenotype spectrum in isolated and syndromic nanophthalmos. Issue 4 (30th September 2020) - Lang, Elena; Koller, Samuel; Atac, David; Pfäffli, Oliver A.; Hanson, James V.M.; Feil, Silke; Bähr, Luzy; Bahr, Angela; Kottke, Raimund; Joset, Pascal; Fasler, Katrin; Barthelmes, Daniel; et al.
Abstract: Purpose: To (i) describe a series of patients with isolated or syndromic nanophthalmos with the underlying genetic causes, including novel pathogenic variants and their functional characterization and (ii) to study the association of retinal dystrophy in patients with MFRP variants, based on a detailed literature review of genotype–phenotype correlations. Methods: Patients with nanophthalmos and available family members received a comprehensive ophthalmological examination. Genetic analysis was based on whole‐exome sequencing and variant calling in core genes including MFRP, BEST1, TMEM98, PRSS56, CRB1, GJA1, C1QTNF5, MYRF and FAM111A . A minigene assay was performed for functional characterization of a splice site variant. Results: Seven patients, aged between three and 65 years, from five unrelated families were included. Novel pathogenic variants in MFRP (c.497C>T, c.899‐3C>A, c.1180G>A), and PRSS56 (c.1202C>A), and a recurrent de novo variant in FAM111A (c.1706G>A) in a patient with Kenny–Caffey syndrome type 2, were identified. In addition, we report co‐inheritance of MFRP ‐related nanophthalmos and ADAR ‐related Aicardi–Goutières syndrome. Conclusion: Nanophthalmos is a genetically heterogeneous condition, and the severity of ocular manifestations appears not to correlate with variants in a specific gene. However, retinal dystrophy is only observed in patients harbouring pathogenic MFRP variants. Furthermore, heterozygous carriers of MFRP and PRSS56 should be screened for the presence of high hyperopia. Identifying nanophthalmos as an isolated condition or as part of a syndrome has implications for counselling and can accelerate the interdisciplinary care of patients.